ANALISIS BIAYA TRANSPORTASI DALAM PENETAPAN TARIF PENGIRIMAN BARANG PADA J&T EXPRESS DP R. H. FISABILILLAH TANJUNGPINANG - Saputra, Novi Chandra; Bailey, Alya Ningsih (Economic, Accounting Scientific Journal (CASH), 2023)
The purpose of this study is to determine the components of transportation costs in determining the delivery rates for J&T Express DP R. H. Fisabilillah Tanjungpinang. The research method in this study uses a type of qualitative research. The type of data used is qualitative data with the data sources used are primary data and secondary data. Data collection techniques using interviews, observation, documentation, and literature studies. Data processing techniques use data collection, data reduction, data  display, conclusion drawing and verification. Data analysis techniques use qualitative descriptive analysis methods. Based on the results of the study, it is known that the J&T Express DP R. H. Fisabilillah Tanjungpinang company sets a freight rate for the type of Regular/Air EZ services subject to a shipping rate of Rp. 36.000 per kg with an estimate delivery time of 3-4 days by plane and the Alternative/Sea ECO services is subject to a shipping rate of Rp. 31.000 per kg with an estimated delivery time of 5-7 days by cargo ship. The conclusion obtained from this study is that the transportation costs at  J&T Express DP R. H. Fisabilillah Tanjungpinang company, especially for Regular/Air EZ services and Alternative/Sea ECO services are formed from cost components in the form of plastic packing costs with a unit price of Rp. 2,000 where this fee is not charged to the customer and in determining the delivery rate of goods is determined based on several components of the calculation, namely the use of the type of service, the weight of the goods, the volume of goods and the distance to the destination city.